2020
DOI: 10.1183/13993003.00912-2020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the renin–angiotensin–aldosterone–SARS-CoV axis: a comprehensive review

Abstract: ImportanceCoronavirus disease 2019 (COVID-19), the disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been declared a global pandemic with significant morbidity and mortality since first appearing in Wuhan, China, in late 2019. As many countries are grappling with the onset of their epidemics, pharmacotherapeutics remain lacking. The window of opportunity to mitigate downstream morbidity and mortality is narrow but remains open. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
153
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 145 publications
(163 citation statements)
references
References 108 publications
2
153
0
8
Order By: Relevance
“…This tissue distribution is consistent with the pathophysiology and clinical features of SARS infection and related disease [3]. ACE2 is a key modulator of the renin-angiotensin-aldosterone system (RAAS), which is a signaling pathway involved in the regulation of vascular and heart function [4].…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This tissue distribution is consistent with the pathophysiology and clinical features of SARS infection and related disease [3]. ACE2 is a key modulator of the renin-angiotensin-aldosterone system (RAAS), which is a signaling pathway involved in the regulation of vascular and heart function [4].…”
Section: Introductionsupporting
confidence: 74%
“…RAAS blockers were, however, also hypothesized to exert protective effects [4]. Indeed, recombinant ACE2 or losartan might counteract both pulmonary edema and the reduced lung function due to decreased expression of ACE2 [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…This was shown as a major factor in the higher case-fatality rates associated with SARS and MERS, when compared to COVID-19 (Wit et al 2016 ). The increase in angiotensin II (AngII) caused by reduced level of angiotensin converting enzyme II (ACE2) membrane protein which is endocytosed along with n-CoV has been implicated in the progression of lung injury and propagation of severe inflammation due to dysregulation of renin-angiotensin pathway (RAS) (Ingraham et al 2020 ). AngII acts as a proinflammatory cytokine via angiotensin-1-receptor (AT1R), the latter also activates NF-κB, disintegrin and metalloprotease 17 (ADAM17) (Devaux et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The virus is known to enter cells via the ACE2 receptor, and may potentially interfere with the renin-angiotensin system in ways that alter pulmonary vascular tone 12 . Although it is reported that later stages of the disease are characterized by downregulation of ACE2 and vasoconstriction (promoting ARDS) [12][13][14] , it is possible that earlier stages instead promote local vasodilation or impairment of HPV 5,15 flow is equal to the fraction of lung with impaired oxygen transport (Fshu:Finj = 1). Heterogeneous 162 perfusion may increase the risk for larger Fshu, especially when the injured region also receives more baseline perfusion (see Figure 2).…”
Section: Discussionmentioning
confidence: 99%